X2-11x-60=0

Simple and best practice solution for X2-11x-60=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2-11x-60=0 equation:



X2-11X-60=0
We add all the numbers together, and all the variables
X^2-11X-60=0
a = 1; b = -11; c = -60;
Δ = b2-4ac
Δ = -112-4·1·(-60)
Δ = 361
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{361}=19$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-19}{2*1}=\frac{-8}{2} =-4 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+19}{2*1}=\frac{30}{2} =15 $

See similar equations:

| 8x-2+5=6(x+1) | | 2(u-6)=9u+44 | | 11x-(4x-3)=17 | | 13x=75+11x | | 6n+13n-15n=0 | | (W-6/4)+6=(w-5/5) | | 8(y+4)=7y | | 2x+15+2x+85=180 | | 8x+3=-2x-128x | | 0.6=0.5+x-0.15 | | 6/a+4=2/7 | | -58+12y+2=5(3y-4)-9 | | 9(c-3)+9=7+c-25 | | 7z-10z=15 | | -3(t+1)=13 | | 3(2n+4)=53 | | (4x+12)/(3)|=4 | | (3x-2)/5=2x-3 | | (D^3-3D+4)y=0 | | 3.7g=-4.45 | | -9x-8=7x+40 | | 5r*2r^2+r=3 | | 5r*2r^2+r=1 | | (X+139)(x+57)=180 | | 3x+12+6=5x-5+1 | | 3.8g=-104.13 | | 3x+12+6=15x-5+1 | | 16a=0.096 | | 3x+12+6=15x-5+ | | 24=4x-8+2x | | Y-11=-1/2(x/ | | Y=|x|+2 |

Equations solver categories